Marketing Strategy Development At Bumikayu Villa And Restaurant - Muhammad Isman (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
Tourism restaurants in West Java are experiencing rapid growth as the number of tourist visits increases and are faced with the challenge of maintaining their attractiveness amidst increasingly fierce competition. Intense competition between restaurants and the need for innovation in concept and service to remain relevant and attractive to tourists. Support from government programs, such as developing tourism infrastructure, will strengthen West Java's position as a leading tourist destination in Indonesia. Innovations in service, including the use of technology for digital ordering and promotions, are expected to help tourism restaurants reach more tourists and increase their contribution to the local economy. The problem that occurred in Bumikayu was that the sales target was not achieved, Bumikayu restaurant had to create a new marketing strategy, so that a new marketing strategy was created to increase restaurant sales. This research aims to help Bumikayu in formulating and implementing marketing strategies that will increase its sales targets and increase competitiveness in the restaurant industry in Garut. The approach used in this research is a qualitative and quantitative approach. The data collection technique was carried out using a survey method via questionnaires for a total sampling of 240 respondents. The data obtained in this research was processed statistically using Structural Equation Modeling Partial Least Square (SEM PLS). The results of hypothesis testing show that combining the elements of product, price, place, promotion, people, process, and physical evidence, when executed effectively, contributes significantly to customer attraction and retention. Thus, the results of this research, theoretically and practically, can be used to indicate the importance of a deep understanding of the target market and customer needs to create a resonant marketing strategy.